Factors determining cultural city tourists' length of stay - Gemar-Castillo, Germán; Sánchez-Teba, Eva María; Soler-García, Ismael Pablo (ELSEVIER, 2022)
This study aims to provide guidelines for decision makers of cultural cities in relation to the determinants of tourists' length of stay, a critical variable of the success of a tourist destination, and a guide for the correct urban planning of the destination. For this purpose, a zero-truncated negative binomial model and a zero-truncated Poisson model with data from 1152 surveys were used. The work reaffirms the use of counting models for this type of study and attempts to discover patterns in tourist destinations to increase the length of stay of tourists. Interesting findings are obtained, such as the causal relationship between being a tourist woman and the length of stay. Also, loyal visitors to the destination and the knowledge of the tourist will be factors that have an impact on a longer length of stay. This will lead to an integral perspective of tourism that includes territorial planning and management.
Keywords: Actividades recreativas; Turismo; Alojamientos turísticos; Planificación urbana; Zero-truncated negative binomial model; Zero-truncated Poisson model; Urban planning; Cultural tourism; Length of stay